1993
DOI: 10.1063/1.108894
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of high concentrations of erbium in crystal silicon

Abstract: High concentrations (≊1020/cm3) of Er have been incorporated in crystal Si by solid phase epitaxy of Er-implanted amorphous Si. This concentration is some 2 orders of magnitude higher than has previously been achieved. During thermal recrystallization of the amorphous layer, segregation and trapping of Er occurs at the moving crystal/amorphous interface. As long as the concentration of Er trapped in the crystal remains below a critical level, perfect epitaxial regrowth occurs. This concentration limit is tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
5

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 14 publications
0
26
0
5
Order By: Relevance
“…6,7 Er-doped silicon is an interesting optoelectronic material, due to optical transitions in the internal 4 f shell of Er 3ϩ , 8 and in order to fully exploit the possibilities of this material, detailed knowledge of the incorporation behavior of Er in Si is required. The equilibrium solubility of Er in c-Si is unknown, but by analogy to the transition metals 9 it is estimated to be 10 14 -10 16 cm Ϫ3 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Er-doped silicon is an interesting optoelectronic material, due to optical transitions in the internal 4 f shell of Er 3ϩ , 8 and in order to fully exploit the possibilities of this material, detailed knowledge of the incorporation behavior of Er in Si is required. The equilibrium solubility of Er in c-Si is unknown, but by analogy to the transition metals 9 it is estimated to be 10 14 -10 16 cm Ϫ3 .…”
Section: Introductionmentioning
confidence: 99%
“…16 At a temperature of 620°C efficient SPE regrowth is occurring and annealing for 3 h ͑treatment B͒ is sufficient for the a-c Si interface to traverse the implanted region. In the absence of O, Polman et al 12 have shown that recrystallization produces a redistribution of Er atoms through the migration of the Er ahead of the a-c interface. This will ultimately lead to the formation of clusters of Er and Si atoms and to the formation of Er silicide precipitates.…”
Section: B Effects Of Different Anneal Treatments On the O Codoped Smentioning
confidence: 99%
“…Recrystallization of the amorphous region will occur once the annealing temperature exceeds the crystallization temperature in Si ͑ϳ550°C͒. 12 Sample O3 only received thermal treatment A and the absence of an EPR signal can be explained in terms of little or no SPE regrowth occurring in this sample. EXAFS measurements on this sample have shown that the six nearest neighbors of Er are all Si and that the local environment is ErSi 2 like.…”
Section: B Effects Of Different Anneal Treatments On the O Codoped Smentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Polman et al 23 have shown that high concentrations of erbium can be achieved by ion-implantation followed by an annealing stage at 600 0 C. The Er incorporated substitutionally in this way can then be optically activated by a subsequent heat treatment step at 1000oC. We have adopted a different approach towards the same goal of large erbium concentrations.…”
Section: Discussionmentioning
confidence: 96%